Founder of Hasidism : a Quest for the Historical Ba'al Shem Tov. - Rosman, Moshe (Littman Library of Jewish Civilization, The, 2013)
Moshe Rosman's award-winning research supplies the history behind the legend of the Ba'al Shem Tov and thus changes the master-narrative of hasidism.